Do the Same Rules Apply? Transferring MOOC Success Behaviors to University Online Learning - Monterozo, Clarence James (Archīum Ateneo, 2023)
In this paper, we replicated the methods and findings of a study on successful completion of massive open online courses (MOOCs) in the context of online learning in a university in Metro Manila, Philippines. Specifically, we examine whether discussion forum behaviors associated with completion in MOOCs also resulted in better outcomes in university online learning courses. To this end, we collected logs from the university's learning management system. The Mann-Whitney U test was used to compare the average scores of those who conformed to these behaviors and those who did not. Pearson's r correlation was then used to determine if a significant relationship exists between each of the measured behaviors and the average scores of the students for each course. The same analyses were then performed for each of the five schools in the same university. The study failed to replicate the results of the MOOC study in all cases. The difference in means was not far apart for all rules. This could be attributed to the difference in pacing and demographic between universities and MOOCs. Despite these, the study still demonstrates that techniques used to study MOOCs can be used to study the behaviors and success indicators of students.